Adverse Childhood Experiences and Substance Use: The Mediating Role of Perceptions of Harm and Peer and Parental Attitudes - Richard, Jérémie; Marchica, Loredana; Sciola, Anthony; Ivoska, William; Derevensky, Jeffrey (International Journal of Child and Adolescent Resilience / Revue internationale de la résilience des enfants et des adolescents)

(untitled) (Canada Research Chair in Interpersonal Traumas and Resilience/Chaire de recherche du Canada sur les traumas interpersonnels et la résilience, 2021)
Objectives: Adverse childhood experiences (ACEs) are related to the development of a range of mental health problems and risky behaviors. Generally, adolescents who experienced a greater number of ACEs have been found to be at increased risk of substance use behaviors. This study investigated the association between ACEs and substance use (i.e., cigarette smoking, binge drinking, and cannabis use) as mediated by perceptions of harm and perceived peer and parental attitudes towards each substance.Methods: A survey was completed by 6,304 students aged 12 to 18 (M = 14.75, SD = 1.76) in Wood County, Ohio, assessing ACEs, substance use behaviors, perceptions of harm and perceived peer and parental attitudes towards each substance. Mediation models controlling for age and gender were conducted for each substance use behavior including perceptions of harm and perceived peer and parental attitudes specific to each substance.Results: Controlling for age and gender, perceptions of harm and peer attitudes towards binge drinking partially mediated the relationship between ACEs and past month binge-drinking. For past month cannabis and cigarette smoking, peer and parental attitudes, but not perceptions of harm, partially mediated the relationship between ACEs and past month engagement in these substances.Implications: Greater perceptions of harm and negative attitudes by parents or peers may be protective against substance use behaviors among youth that have experienced ACEs. Early interventions focusing on increasing perceptions of harm along with promoting negative parental and peer attitudes towards substance use could decrease rates of use among those who experienced ACEs.